Enhancing firm competitiveness in fast track through total productive maintenance. (10th December 2010) - Sardana, G.D.; Sinha, S.K.
Competitiveness is a major challenge before a company. Simply stated competitiveness of a firm refers to firstly management of capabilities to exploit its resources, competencies and knowledge and secondly to manage change with the overall objectives of adapting better and faster than competition. Superior manufacturing performance of a firm leads to competitiveness. Business environment in the last decade has changed radically in India. With the advent of WTO regime of globalisation and liberalised trade, the heavily protected Indian industry has had to face competition both from within as well as established companies practicing world-class techniques. This paper provides an analysis of how National Engineering Industries (NEI), a medium-sized company in India, has reacted to a changing market environment and transformed itself to remain competitive following a focused approach in implementing total productive maintenance.